2015
DOI: 10.1159/000442192
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Factors Related to the Prognosis of Metastatic Breast Cancer Patients after Development of Brain Metastasis

Abstract: Background: The prognosis of breast cancer patients with brain metastasis (BM) is extremely poor, and the survival after development of BM is very short. We aimed to investigate clinicopathological factors related to significant effects on the prognosis after BM development. Patients and Methods: This is a retrospective study of 75 early breast cancer patients who received the standard of care and subsequently developed BM. Results: Breast cancer subtype was one of the significant predictors for prognosis afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Traditional prognostic factors include age, menopausal status, status of axillary lymph nodes, tumor size, histological features, and estrogen and progesterone receptors (6), and the prognosis of breast cancer is closely associated with the invasion and metastasis early on. It is reported that peritoneal metastases (7,8), lymph node metastasis (9,10) and brain metastasis (11)(12)(13) in breast cancer are usually associated with a poor prognosis following standard treatments. The progression, invasion and metastasis of breast cancer involve multiple genetic mutations, leading to the activation of oncogenes and the inactivation of tumor suppressor genes (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional prognostic factors include age, menopausal status, status of axillary lymph nodes, tumor size, histological features, and estrogen and progesterone receptors (6), and the prognosis of breast cancer is closely associated with the invasion and metastasis early on. It is reported that peritoneal metastases (7,8), lymph node metastasis (9,10) and brain metastasis (11)(12)(13) in breast cancer are usually associated with a poor prognosis following standard treatments. The progression, invasion and metastasis of breast cancer involve multiple genetic mutations, leading to the activation of oncogenes and the inactivation of tumor suppressor genes (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HER2 positive lived longer than those with negative HER2 (median time 11 vs. 6 months). Yamamura et al ( 20 ) conducted research into 75 early BC patients subsequently developing brain metastasis. The results indicated that luminal HER2 cancer, favorable PS and single metastatic brain tumor independently affected the prognosis of those patients.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to the efficacy, there are various outcomes in different studies in this review. It could be found in some studies that adjuvant therapies, including chemotherapy, endocrine therapy, targeted therapy and radiotherapy, could prolong the survival time of patients with MBC, while there still are some studies not revealing the significant benefits on survival from systemic treatment (1,2,7,8,(18)(19)(20)(21)24). However, due to the fact that most studies included are single-center studies, it is inevitable for the existence of patient selection bias, which would disturb the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that breast cancer patients with brain metastasis (BM) have a very poor prognosis and a short survival time following BM [9]. However, much progress has been made regarding the diagnosis of the condition, especially with the application of PET-CT and MRI [10].…”
Section: Discussionmentioning
confidence: 99%